1995
DOI: 10.1111/j.1476-5381.1995.tb13276.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the vascular endothelium on noradrenaline‐induced contractions in non‐pregnant and pregnant guinea‐pig uterine arteries

Abstract: 1 The effect of pregnancy on noradrenaline-mediated contraction of guinea-pig uterine artery rings with both intact and denuded endothelium was investigated.2 Noradrenaline (25 nM -I00 #Lm) induced concentration-dependent contraction of non-pregnant and pregnant guinea-pig uterine arterial rings with intact endothelium with similar pD2 and maximal response values (non-pregnant: pD2= 5.85 ± 0.02, maximal response = 121 ± 8.2%; pregnant: pD2 = 5.81 ± 0.04, maximal response = 122 + 9.1%). Removal of endothelium d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This may be due to the high intrinsic activity of acetylcholine that may result in difficulties to block NO‐synthase activity in the presence of such a strong agonist (Jovanović et al., 1994c). The release of a, yet unidentified, endothelium‐dependent relaxant factor may also be alternatively possible (Jovanović et al., 1995b).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the high intrinsic activity of acetylcholine that may result in difficulties to block NO‐synthase activity in the presence of such a strong agonist (Jovanović et al., 1994c). The release of a, yet unidentified, endothelium‐dependent relaxant factor may also be alternatively possible (Jovanović et al., 1995b).…”
Section: Discussionmentioning
confidence: 99%
“…The increased α 2 -mediated vasorelaxation was dependent on the endothelium and nitric oxide synthase (NOS). Several studies in isolated uterine arteries from pregnant humans and various experimental animal models [51][52][53][54][55][56][57] have demonstrated that endothelium-dependent and independent pathways play increased roles in buffering adrenergic receptor-induced vasoconstriction in pregnant versus non-pregnant groups. These enhanced vasodilatory and vasoconstriction-buffering mechanisms are mediated by increased NOS, vascular smooth muscle cell responsiveness to vasodilators, and reduced capacity of the smooth muscle layer to depolarize [54,58].…”
Section: Mechanisms To Buffer Sna-mediated Control Of Maternal Hemodynamics During Normal Pregnancymentioning
confidence: 99%
“…It is known that cardiac output is increased during pregnancy, which is associated with increased rates of perfusion to both reproductive and non-reproductive organs (Rosenfeld, 1977). This vascular adaptation of mothers to pregnancy is considered to be due to blunted vascular response to vasoconstrictors on the one hand (Weiner et al, 1991;Grbovic ´and Jovanovic ´, 1996Jovanovic ´et al, 1998b), and increased response to vasodilators on the other (Weiner et al, 1989), although this concept has been repeatedly challenged (Jovanovic ´et al, 1994a(Jovanovic ´et al, , 1995a(Jovanovic ´et al, ,b,c, 1997.…”
Section: Introductionmentioning
confidence: 99%